Effects of a cooling collar on affect, ratings of perceived exertion, and running performance in the heat - Minniti, A.; Tyler, C. T.; Sunderland, C. (European Journal of Sport Science, 2011)
During prolonged exercise, ratings of perceived exertion (RPE) and affect (pleasure; activation) play an important role in performance, especially in hot conditions. Although various mechanisms have been tried to manage the effects of heat (e.g. cooling jackets), the purpose of the current research was to assess the effect of a cooling collar on RPE, affect, thermal sensation, and running performance in the heat. Participants (n =8) wore a cold collar, uncooled collar or no collar as they completed three 90-min preloaded treadmill time-trials in the heat (30.5±0.1°C), which included 75 min at appr. 60% [Vdot]O2max followed by a 15-min time-trial. Affect, RPE, and thermal sensation were measured throughout. Performance during the time-trial was significantly improved in the cold collar compared with the uncooled collar and no-collar trials; however, pleasure and activation ratings were highest for the no-collar trial. Findings suggest that a cooling collar may improve performance, but not necessarily "feel good". Practically, it seems necessary to ensure sufficient education about the benefits, on balance, of the cold collar, while the performance improvements outweighed the reported discomfort of athletes in this study. In addition, the cold collar may prove quite beneficial for individuals who work in hot climates and or conditions, as it may be effective in minimizing discomfort associated with heat for other groups as well.